Penerapan Prinsip Kehati-Hatian dalam Perjanjian Kredit Pemilikan Rumah pada Bank Tabungan Negara Cabang Kupang - Renaldi Takoy; Orpa J. Nubatonis; Chatryen M. Dju Bire (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the procedures for implementing housing credit agreements and the application of the prudential principle in housing credit agreements at Bank Tabungan Negara Kupang Branch. This research uses an empirical juridical method. The results show that the KPR lending procedure at Bank Tabungan Negara Kupang Branch normatively follows the standard stages of credit procedures and fulfills the legal validity requirements of agreements as stipulated in the Indonesian Civil Code, banking regulations, and provisions established by the Financial Services Authority of Indonesia. The prudential principle is implemented through the 5C credit analysis, Financial Information Service System (SLIK) checks, document verification, debtor repayment capacity analysis, collateral assessment, and multi-level credit approval mechanisms. However, substantively several weaknesses are still found, including limitations in verifying the debtor’s character, inaccuracies in credit analysis data, and a high reliance on administrative documents. Furthermore, the use of standard form contracts in credit agreements indicates an imbalance in bargaining positions between the bank and the debtor. These findings indicate that the prudential principle has been implemented procedurally but has not yet been fully optimal in mitigating risks substantively.